2021
DOI: 10.3389/fonc.2021.622752
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Immunometabolism Characterization in Ovarian Cancer With Prognostic and Therapeutic Implications

Abstract: Metabolic dysregulation in the tumor microenvironment has significant impact on immune infiltration and immune responses. However, interaction between immunity and metabolism in the ovarian microenvironment requires further exploration. We constructed an immunometabolism gene set and ovarian cancer cohort from The Cancer Genome Atlas (TCGA) and classified these into three immunometabolism subtypes. We explored the relationships between immune infiltration and metabolic reprogramming. Additionally, we built ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…Furthermore, the WNT/β-catenin signaling pathway is also correlated with resistance to anti-PD-L1 and anti-CTLA4 combined therapy [ 80 ]. Studies have also explored the interaction of metabolism and tumor-immune subtypes [ 81 ]. It has been suggested that upregulation of hormone biosynthesis and low immune cell infiltration are the two main characteristics of the ‘immune-desert–endocrine subtype’, which is negatively correlated with MHC molecules and multiple immune cells, such as dendritic cells, and finally leads to the immune-desert type [ 81 ].…”
Section: Mechanisms Of Cafs In the Progression Of Ovarian Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the WNT/β-catenin signaling pathway is also correlated with resistance to anti-PD-L1 and anti-CTLA4 combined therapy [ 80 ]. Studies have also explored the interaction of metabolism and tumor-immune subtypes [ 81 ]. It has been suggested that upregulation of hormone biosynthesis and low immune cell infiltration are the two main characteristics of the ‘immune-desert–endocrine subtype’, which is negatively correlated with MHC molecules and multiple immune cells, such as dendritic cells, and finally leads to the immune-desert type [ 81 ].…”
Section: Mechanisms Of Cafs In the Progression Of Ovarian Cancermentioning
confidence: 99%
“…CXCR2 ligands, including CXCL1 and CXCL2, attract MDSC infiltration in Snail-expressing mice to promote ovarian cancer progression [ 82 ]. Metabolic stress may stimulate impaired antitumor immunity in immune-infiltrating tumors [ 81 ]. iCAF subsets also produce certain cytokines, especially IL-6, which presents a pro-tumor function and is closely associated with chemoresistance and poor prognosis [ 83 ].…”
Section: Mechanisms Of Cafs In the Progression Of Ovarian Cancermentioning
confidence: 99%
“…An increasing number of studies have indicated that metabolic reprogramming of tumors is related to immune infiltration and immune responses (16). Therefore, we further investigated whether there were different subgroups of immune cells in the two risk groups and scored the related functions by using ssGSEA.…”
Section: Functional Analysesmentioning
confidence: 99%
“…Approximately 70% of OC individuals will develop a recurrence after surgery, and about 75% of high-grade serous ovarian cancer (HGSOC) patients will experience chemoresistance against cisplatin, oxaliplatin, carboplatin, etc. [9,10]. Identifying novel risk factors that regulate tumorigenesis, migration, and proliferation will contribute to early diagnosis and personalized interventions for OC treatment.…”
Section: Introductionmentioning
confidence: 99%